2017
DOI: 10.21894/jopr.2017.2901.06
|View full text |Cite
|
Sign up to set email alerts
|

EFFICACY OF PHEROMONE TRAPPING AND AERIAL SPRAYING OF Bacillus thuringiensis (Bt) FOR CONTROLLING BAGWORM, Metisa plana WALKER (Lepidoptera: Psychidae) IN YONG PENG, JOHOR, MALAYSIA

Abstract: Recurring bagworm outbreak is a major problem in the oil

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 1 publication
0
5
0
2
Order By: Relevance
“…Control of O. rhinoceros by using entomopathogens is an alternative when the use of synthetic chemical insecticides is not able to solve pest problems. For example, Bacillus thuringiensis used to pest control has been tried to control Metisa plana caterpillars (Khaeruni and Purnamaningrum 2012;Ahmad et al 2017;), but to controlling O. rhinoceros is still not much studied.…”
Section: Introductionmentioning
confidence: 99%
“…Control of O. rhinoceros by using entomopathogens is an alternative when the use of synthetic chemical insecticides is not able to solve pest problems. For example, Bacillus thuringiensis used to pest control has been tried to control Metisa plana caterpillars (Khaeruni and Purnamaningrum 2012;Ahmad et al 2017;), but to controlling O. rhinoceros is still not much studied.…”
Section: Introductionmentioning
confidence: 99%
“…Chemical insecticides application through trunk injection technique, ground spraying technique, and aerial spraying includes the use of trichlorfon, cypermethrin, methamidophos, and monocrotophos [ 14 ]. The use of biopesticides, such as Bacillus thuringiensis ( Bt ) [ 15 , 16 ], endoparasitoid [ 17 ], and pheromone mass trapping as a biological control [ 18 ] have been reported. Despite these efforts, effective control with economical benefits and safer choice is yet to be found.…”
Section: Introductionmentioning
confidence: 99%
“…Present studies are in correlation with the studies of Trissolcus a hymenopteran insect 26 . The studies on this insect have shown that virgin male Trissolcus have shown a positive response to Tetradecyl acetate, Ethyl (Z)-9-hexadecenoate GC-EAD components on exposure to EAG machine 27 . Present results also show that the number of Xanthopimpla trapped was more in the third crop than first and second crops.…”
Section: Rearing Of Anthereae Mylitta Drurymentioning
confidence: 99%